‘Friend-or-foe’ in the ‘Diplomatic’ Painting of the Renaissance Venice - Chechik, Liya A. (Actual Problems of Theory and History of Art, 2025)
In the history of culture the unique image of Venice was emerging during a thousand years. It was forming in parallel with the “myth of Venice”, a critical component of which was the main idea of Venice as a bridge between East and West. The article defines the features of Venetian artists rendering images of the Muslim world in secular painting of the Renaissance.
Keywords: Venice; East; diplomatics; 'friend-or-foe'; Renaissance painting